Modeling and Optimization of Advanced Manufacturing Processes - Bhowmik, Sumit; Jagadish; Gupta, Kapil; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book covers various multiple-criteria decision making (mcdm) methods for modeling and optimization of advanced manufacturing processes (AMPs). Processes such as non-conventional machining, rapid prototyping, environmentally conscious machining and hybrid machining are finally put together in a single book. It highlights the research advances and discusses the published literature of the last 15 years in the field. Case studies of real life manufacturing situations are also discussed.
Introduction -- Modeling and Optimization of Electrical Discharge Machining -- Modelling and optimization of abrasive water jet machining process -- Modeling and Optimization of Ultrasonic Machining Process -- Modeling and Optimization of Rapid Prototyping Process.
Keywords: Manufactures; Ceramic materials; Machinery; Metals; Machines, Tools, Processes; Ceramics; Machinery and Machine Elements; Metals and Alloys